2011
DOI: 10.1128/jcm.02362-10
|View full text |Cite
|
Sign up to set email alerts
|

Human Bocavirus as the Cause of a Life-Threatening Infection

Abstract: Human bocavirus is a recently described respiratory pathogen. A case of a life-threatening human bocavirus infection of a previously healthy pediatric patient is described. An initial clinical presentation of acute bronchiolitis developed into an extremely severe course of disease characterized by pneumothorax, pneumomediastinum, and acute respiratory failure with pronounced air-leak syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
64
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 23 publications
5
64
1
2
Order By: Relevance
“…However, while HBoV-1 infection is frequent and shedding may be long-lasting in infants and toddlers, primary HBoV-1 infections are comparably rare among 4-year-olds, making such a coincidence unlikely. The presentation was very similar to a recently published case also linked to HBoV-1 (12). Thus, we find it likely that the observed primary HBoV-1 infection did cause the symptoms.…”
Section: Case Reportsupporting
confidence: 87%
See 1 more Smart Citation
“…However, while HBoV-1 infection is frequent and shedding may be long-lasting in infants and toddlers, primary HBoV-1 infections are comparably rare among 4-year-olds, making such a coincidence unlikely. The presentation was very similar to a recently published case also linked to HBoV-1 (12). Thus, we find it likely that the observed primary HBoV-1 infection did cause the symptoms.…”
Section: Case Reportsupporting
confidence: 87%
“…Thus, blood testing is crucial for studying HBoV-1 and disease, and new studies applying adequate diagnostic testing are urgently required. Ursic et al (12) recently reported on a 20-month-old child who presented with acute bronchiolitis that developed into a severe course characterized by pneumothorax, pneumomediastinum, and respiratory failure with air-leak syndrome, a clinical course very similar to that of the present case. The solid diagnostic workup included electron microscopy and monitoring of HBoV-1 DNA in upper and lower respiratory secretions and plasma (12).…”
Section: Case Reportsupporting
confidence: 76%
“…HBoV1 causes lower respiratory tract infections, especially in infants less than 2 years old (3)(4)(5)(6)(7). Severe and deadly cases associated with high viral load, anti-HBoV1 IgM antibody detection, or increased IgG antibody production have been documented (7)(8)(9). In vitro, HBoV1 infects polarized primary human airway epithelium cultured at an airliquid interface (HAE-ALI) (10) and causes damage to the airway epithelium (11)(12)(13).…”
mentioning
confidence: 99%
“…HBoV has also been reported to associate with acute wheezing and encephalitis (31,32). Two cases of life-threatening HBoV infection have been described recently, suggesting that HBoV most likely plays a role in severe and lethal diseases (33,34). The genome of HBoV contains three open reading frames, encoding four proteins, among which VP2 shares the same sequence with VP1, and only differs in the N-terminal extension (35).…”
mentioning
confidence: 99%